Developmental Coordination Disorders and Cooccurring: knowing the “state of the art” (Research, Society and Development, 2021)
The objective of the work was to know the state of the art involving DCD and the co-occurrence of other Developmental Disorders. This is an integrative review study involving the following databases: Sport Discus, Gale Academic, Google Scholar, Medline, Science Direct and Scopus through the journal portal of the Coordination for the Improvement of Higher Education Personnel (CAPES). The descriptors used were: Developmental Coordination Disorder AND Co-occurrences AND Comorbidity; Developmental Disabilities AND Co-occurrences OR Comorbidity AND Developmental Coordination Disorder, from 2000 to 2020, in English. The final sample consisted of 06 articles and the results showed that there is little research related to co-occurrences with DCD; the developmental phases present were childhood and adolescence and there are several tests that can help to identify developmental disorders. We conclude that the subject in question has received little attention from scholars in the field despite the assertion that the co-occurrence between DCD and Developmental Disorders is frequent and not an exception.